Human sensitivity to differences in the rate of auditory cue change - Maloff, Erin S. (Acoustical Society of America, 2013)
Measurement of sensitivity to differences in the rate of change of auditory signal parameters is complicated by confounds among duration, extent, and velocity of the changing signal. Dooley and Moore [(1988) J. Acoust. Soc. Am. 84(4), 1332–1337] proposed a method for measuring sensitivity to rate of change using a duration discrimination task. They reported improved duration discrimination when an additional intensity or frequency change cue was present. The current experiments were an attempt to use this method to measure sensitivity to the rate of change in intensity and spatial position. Experiment 1 investigated whether duration discrimination was enhanced when additional cues of rate of intensity change, rate of spatial position change, or both were provided. Experiment 2 determined whether participant listening experience or the testing environment influenced duration discrimination task performance. Experiment 3 assessed whether duration discrimination could be used to measure sensitivity to rates of changes in intensity and spatial position for stimuli with lower rates of change, as well as emphasizing the constancy of the velocity cue. Results of these experiments showed that duration discrimination was impaired rather than enhanced by the additional velocity cues. The findings are discussed in terms of the demands of listening to concurrent changes along multiple auditory dimensions.